Rumination and posttraumatic stress symptoms in trauma-exposed adults: a systematic review and meta-analysis. Issue 4 (4th July 2017) - Szabo, Yvette Z.; Warnecke, Ashlee J.; Newton, Tamara L.; Valentine, Jeffrey C.
ABSTRACT: Background and objectives : Rumination is a correlate of increased posttraumatic stress (PTS) symptoms. This study quantitatively reviewed the literature on rumination and PTS symptoms in trauma-exposed adults, extending prior research by using an inclusive definition of trauma, addressing PTS symptom clusters, and conducting moderator analyses. Method: Searches were conducted in PsycINFO, PubMed, PILOTS, EBSCO Psychology and Behavioral Sciences Collection, Google Scholar, and Dissertation Abstracts. Sixty-four unique samples from 59 articles were included. Results : Results showed a moderate, positive relationship between rumination and PTS symptoms ( r = .50, p < .001). This was not moderated by time since trauma, gender, prior trauma history, Criterion A congruence of events, type of rumination or PTS symptom measure, or sample setting. However, trauma-focused rumination yielded smaller effect sizes than trait rumination. The association between rumination and intrusive re-experiencing was stronger than that between rumination and avoidance ( t (13) = 9.18, p < .001), or rumination and hyperarousal ( t (9) = 2.70, p = .022). Conclusions : Results confirm that rumination is associated with increased PTS symptoms. Future research should identify mechanisms underlying this association and their potential specificity by symptoms cluster, as well as further examine the potential moderating roles of gender and prior trauma history.